Review: Traditional ecological knowledge of tribal communities of North East India - H tynsong; M Dkhar; BK Tiwari (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Tynsong H, Dkhar M, Tiwari BK. 2020. Review: Traditional ecological knowledge of tribal communities of North East India. Biodiversitas 21: 3209-3224. Traditional ecological knowledge (TEK) refers to the knowledge, innovations and practices of indigenous and tribal people relating to the understanding of structure and functioning of neighboring natural ecosystems and their use for human welfare. In this paper, we have reviewed the literature relating to TEK held by the tribal and other traditional societies of North East India. The region is very rich in TEK pertaining to species, ecosystems, and their interactions including their sustainable management and utilization in forestry, fisheries, agriculture, food, crafts, dye, and health care. Some of these TEK based knowledge systems are at par or even superior to the resource management practices evolved under the ambit of modern knowledge. Though a substantial chunk of TEK of tribal communities of North East India has been documented, huge treasures of such knowledge remain unreported and hence are on the verge of being lost.